2009
DOI: 10.1002/mus.21308
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and pain in patients with facioscapulohumeral muscular dystrophy

Abstract: The aim of this study was to assess quality of life (QoL) and evaluate the occurrence and characteristics of pain in facioscapulohumeral muscular dystrophy (FSHD) patients. No study has yet assessed QoL in a large group of FSHD patients and, overall, few studies have assessed pain in neuromuscular diseases. We performed a prospective study using a multidimensional protocol including: clinical (according to the Clinical Severity Scale Rev1); genetic (p13E-11 EcoRI fragments Rev1); QoL (Short Form-36); pain (Vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 38 publications
12
72
1
Order By: Relevance
“…Another common feature of HRQoL-impairment in studied NMDs was the more pronounced reduction of scores in the HRQoL-domains related to physical health (physical functioning, physical role). This finding is consistent with the results of previous studies [20,21,30]. Progressive muscle degeneration in NMDs results in reduced physical activity and decreased HRQoL related to physical health.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Another common feature of HRQoL-impairment in studied NMDs was the more pronounced reduction of scores in the HRQoL-domains related to physical health (physical functioning, physical role). This finding is consistent with the results of previous studies [20,21,30]. Progressive muscle degeneration in NMDs results in reduced physical activity and decreased HRQoL related to physical health.…”
Section: Discussionsupporting
confidence: 95%
“…The number of studies on other NMDs is considerably lower and only a few are available for myasthenia gravis (MG) and facioscapulohumeral muscular dystrophy (FSHD). In these diseases, a reduction of scores on the SF-36 was found in the domains ''physical functioning'', ''physical role'', ''vitality'', and ''general health'', and in the physical composite score [21,30,31,34,35,38]. The results for domains related to mental health have been inconsistent.…”
Section: Presents a Summary Of Hrqolstudies In Nmds On The Examples Omentioning
confidence: 85%
“…Both reported poorer QoL in the more functionally impaired group on at least one QoL domain, but with no significant differences in emotional functioning [16,28]. Seven studies [7,9,13,15,21,24,25] assessed associations between measures of function and QoL; all reported strong and/or significant associations between physical domains and function. Of these seven, two studies [24,25] reported significant correlations of weak to moderate strength between function and SIP psychosocial.…”
Section: Disease Severitymentioning
confidence: 96%
“…All 12 studies which compared people with MD to healthy controls reported poorer scores for the MD groups on one or more QoL domains [6,7,9,13,[15][16][17][18][19][20][21][22], with five of these studies reporting significantly lower QoL across all sub-scales of the QoL measure [6,7,15,21,22].…”
Section: Qol In MD Compared To Healthy Populationsmentioning
confidence: 99%
See 1 more Smart Citation